Korupsi Perspektif Ibn ‘Asyur: Studi Analisis Tematis dalam Tafsir at-Tahrir wa at-Tanwir - Rizki, Qadar; al-Munawwar, Said Agil Husin; Ulhaq, M. Ziyad (STAINI Press, 2025)
The issue of corruption prevalent in society today is considered a normal and common occurrence, institutionalized, and nearly pervasive in all aspects of community life. One of the anti-corruption eradication methods recommended in Indonesia is the discourse of anti-corruption in religious contexts, as the voice of religion is still quite audible and believed to be effective. The anti-corruption discourse for Muslims is certainly viewed through the lens of the Qur'an. Although the Qur'an does not explicitly mention verses about corruption, there are several verses that indicate issues related to it in addressing the problem of corruption. The method used in this study is a qualitative approach, based on literature research, the verses of the Qur'an, publications in the form of research results, journals, seminars, and articles. The method of interpreting the verses related to corruption employed is the interpretation method of Ibn ‘Asyur. Based on this, in this article, the author attempts to elaborate on the concepts of the Qur'an pertaining to corruption through the commentary of Ibn ‘Asyur via thematic interpretation studies, finding that the terms of corruption explained by Ibn ‘Asyur are very detailed from the aspects of language, Qira’at, and the context of the verses' revelation. Thus, it is easily understood that corruption is prohibited in Islam, and the solution to prevent it lies in implementing religious norms in all aspects of communal life.